Screening Sesbania for response to N and P combinations and adaptability in a medium-altitude environment in Malawi - Kanyama-Phiri, G.Y.; Dzowela, B.H.; Kategile, J.A. (International Livestock Centre for Africa, 1993)
Growth parameters and dry-matter yield of Sesbania sesban and S. goetzei accessions were evaluated for adaptability and response to various nitrogen (N) and phosphorus (P) combinations. N and P fertilisation significantly increased canopy height, growth rate, number of primary branches per plant, stem diameter, leaf and fuelwood dry-matte ryield. This suggests that conservative starter doses of these macro-elements are essential for successful establishment, early growth and subsequent yield of Sesbania. Growth rate declined with advancing season and the onset of drought. A rate of 40 kg N/ha either singly or in combiantion with 50 kg P/ha resulted in a heavier loss of leaves as compared with either a rate of 50 kg P/ha or no fertiliser at all. Nitrogen seemed to increase leaf surface area which placed the plant at a disadvantage when mositure become limiting. These results provide a basis for more elaborate investigation involving more levels of combined N and P, with and without inoculation. The role of moisture stress on the growth behaviour and yield of the two Sesbania species studied warrants further investigation.